FILSAFAT ILMU DAN ARAH PENGEMBANGAN PANCASILA: RELEVANSINYA DALAM MENGATASI PERSOALAN KEBANGSAAN - Kirom, Syahrul (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Study about Pancasila as an Indonesian way of life through the philosophy of science is very important when it is related to national problems nowadays. The philosophy of science which has three aspects (ontology, epistemology and axiology) can be used as a tool to solve the national problems, especially in case of corruption. The solution provides an understanding of Pancasila values.The result of study about the values of Pancasila from the philosophy of science, they are : first, the ontology, Pancasila has teachings and values, such as developing an attitude of respect among human being; second, the epistemology, Pancasila has sources of knowledge and concepts of nationalism that should be used as a guidance in the social life of Indonesia; third, the axiology, the values of Pancasila have a contribution in the lives of Indonesian people through the noble values in social justice and humanity.Keywords: Pancasila, Philosophy of Science, Ontology, Epistemology, Axiology.